Respon Pertumbuhan Vegetatif Ubi Kayu (Manihot esculenta Crantz.) Varietas Ketan Pada Dosis Dan Waktu Pemberian Pupuk Organik Cair (POC) Darah Sapi Terfortifikasi - Novianto (Indoensia), esna dilli; oktasari (Indoensia), wike; khuriyah (Indoensia), azimatul (JURNAL VIGOR, 2024)
Cassava is a carbohydrate-rich crop with significant potential as a staple food. However, cassava production has declined due to suboptimal cultivation practices. This study aims to analyze the interaction between the dosage and timing of fortified liquid organic fertilizer (LOF) from cow’s blood on the growth of cassava plants (Manihot esculenta Crantz.). The experimental design used in this study was a factorial completely randomized design (3x3 m) with 3 replications. The first treatment was the dosage of liquid organic fertilizer from cow’s blood (0 mL, 10 mL, 20 mL, 30 mL), and the second treatment was the timing of liquid organic fertilizer from cow’s blood application (every 3 weeks, every 6 weeks, every 9 weeks). The data obtained were analyzed using analysis of variance and further analyzed using an Orthogonal Polynomial test. The dosage of organic fertilizer did not significantly affect all parameters. The timing of liquid organic fertilizer application only affected the leaf protein content (8,08 %). The dosage and timing of liquid organic fertilizer application significantly affected leaf protein content (%), leaf wet weight (g), leaf dry weight (g), but did not significantly affect plant height (cm), number of leaf, number of shoot, photosynthesis rate (µmol/m2/s), and chlorophyll content (mg/g). The dosage and timing of liquid organic fertilizer application resulted in a protein content of 2,76 %, leaf wet weight of 2,54 g, and leaf dry weight of 2,74 g.